Polarized images of synchrotron radiations in curved spacetime - Zezhou Hu; Yehui Hou; Haopeng Yan; Minyong Guo; Bin Chen (European Physical Journal C: Particles and Fields, 2022)
Abstract In this work, we derive two formulas encoding the polarization direction and luminosity of synchrotron radiations from the moving electrons in curved spacetime under the geometric optics approximation. As an application, we further study the polarized images of synchrotron radiations from electron sources in Schwarzschild black hole spacetime with a vertical and uniform magnetic field. In particular, by focusing on the circular orbits of electrons on the equatorial plane, we show the polarized images of the synchrotron radiations from these orbits for different observational angles and discuss the variations of the polarization directions concerning the angles.